(untitled) (Reflection and Critique Law Magazine, 2020)
This article aims to address the paradigmatic transition of international law and the structural resignification of its concept based on universalist ideals, with the formation of a universal public order that has as its central concern the guarantee of human rights to individuals, regardless of state and national borders. domestic law. To this end, the judgment of the Inter-American Court of Human Rights handed down in the case of Gomes Lund et al. Brazil, in which there is international accountability of the Brazilian State for the violent episodes that occurred during the military dictatorship, which resulted in the death of approximately seventy people, in addition to forced disappearances and torture practiced in the context of the authoritarian regime. In addition, the paper intends to affirm the importance of democracy as a political regime that guarantees citizens freedom and participation, as well as the contributions of international law to the stabilization of a collective memory in Brazilian society, based on the effective guarantee of the right to memory and the truth about the events that occurred in the Guerrilha do Araguaia.